Seed Production of Annual Phlox - Jeffrey G. Norcini; James H. Aldrich (EDIS)
Phlox drummondii Hooker, commonly known as annual or Drummond phlox is one of north and central Florida's showiest and most reliable spring flowering annuals. This document is ENH 1020, one of a series of the Environmental Horticulture Department, UF/IFAS Extension. Original publication date December 23, 2005.